Structure, expression profile and phylogenetic inference of chalcone isomerase-like genes from the narrow-leafed lupin (Lupinus angustifolius L.) genome - Przysiecka, Łucja; Książkiewicz, Michał; Wolko, Bogdan; Naganowska, Barbara (Frontiers in Plant Science, 2015)
Lupins, like other legumes, have a unique biosynthesis scheme of 5-deoxy-type flavonoids and isoflavonoids. A key enzyme in this pathway is chalcone isomerase (CHI), a member of CHI-fold protein family, encompassing subfamilies of CHI1, CHI2, CHI-like (CHIL), and fatty acid-binding (FAP) proteins. Here, two Lupinus angustifolius (narrow-leafed lupin) CHILs, LangCHIL1 and LangCHIL2, were identified and characterized using DNA fingerprinting, cytogenetic and linkage mapping, sequencing and expression profiling. Clones carrying CHIL sequences were assembled into two contigs. Full gene sequences were obtained from these contigs, and mapped in two L. angustifolius linkage groups by gene-specific markers. Bacterial artificial chromosome fluorescence in situ hybridization approach confirmed the localization of two LangCHIL genes in distinct chromosomes. The expression profiles of both LangCHIL isoforms were very similar. The highest level of transcription was in the roots of the third week of plant growth; thereafter, expression declined. The expression of both LangCHIL genes in leaves and stems was similar and low. Comparative mapping to reference legume genome sequences revealed strong syntenic links; however, LangCHIL2 contig had a much more conserved structure than LangCHIL1. LangCHIL2 is assumed to be an ancestor gene, whereas LangCHIL1 probably appeared as a result of duplication. As both copies are transcriptionally active, questions arise concerning their hypothetical functional divergence. Screening of the narrow-leafed lupin genome and transcriptome with CHI-fold protein sequences, followed by Bayesian inference of phylogeny and cross-genera synteny survey, identified representatives of all but one (CHI1) main subfamilies. They are as follows: two copies of CHI2, FAPa2 and CHIL, and single copies of FAPb and FAPa1. Duplicated genes are remnants of whole genome duplication which is assumed to have occurred after the divergence of Lupinus, Arachis, and Glycine.